Association of Hepatic Global DNA Methylation and Serum One‐Carbon Metabolites with Histological Severity in Patients with NAFLD. Issue 1 (29th November 2019) - Lai, Zhiwei; Chen, Junliang; Ding, Chenghe; Wong, Kwanshu; Chen, Xingyi; Pu, Liuzhen; Huang, Qiangwei; Chen, Xiaolin; Cheng, Zijian; Liu, Yan; Tan, Xuying; Zhu, Huilian; et al.
Abstract : Objective: Clinical relevance of global DNA methylation and one‐carbon metabolite levels with histological severity remains uncertain in patients with nonalcoholic fatty liver disease (NAFLD). This study aimed to evaluate hepatic global DNA methylation and serum one‐carbon metabolite concentrations in patients with NAFLD and the possible associations of these parameters with liver histology. Methods: Liver biopsies from 18 control participants and 47 patients with NAFLD were evaluated. Results: The hepatic global DNA methylation level was significantly lower in the NAFLD group than in the control group among participants with overweight. Participants with moderate inflammation and mild fibrosis had significantly lower levels of global DNA methylation than those without these characteristics. Participants with borderline nonalcoholic steatohepatitis had significantly lower global DNA methylation levels than controls. The hepatic global DNA methylation level tended to decrease with the increasing hepatic inflammation grade and disease progression. The NAFLD group had a significantly higher serum homocysteine concentration than the control group among participants with overweight. This level tended to increase with increasing hepatic steatosis grade and disease progression. Conclusions: Patients with NAFLD exhibited lower hepatic levels of global DNA methylation and elevated serum homocysteine concentrations, which are associated with the histological severity of NAFLD.